La révolte de Coro : les catégories bouleversées à l’ère des révolutions (Venezuela, 1795) - Frédéric Spillemaeker (Centre de Recherches sur les Mondes Américains, 2019)
The Coro rebellion in 1795 is often viewed as a mere consequence of the Saint-Domingue Revolution in Venezuela. But it is also a fascinating case to understand the using of the categories during the Age of Revolutions. The fear of the Caribbean Revolution and the pursuit of loyalty were prominent for the interpretation and repression of the rebellion by the authorities. Nevertheless, the Amerindians, the slaves and the free people of colour could adopt other different tactics, beyond assignation and categorization.